Labor absorptive capacity of export expansion and import substitution in Egypt, 1954 to 1970 - Maurice Girgis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1973)
In the post war era, much has been said about the role of the foreign trade sector in affecting the rate and the level of domestic economic growth in the group of LDCs. The impact of exports in particular received the lion's share of attention. It has been frequently argued that exports act as an engine of growth. The line of causation here runs from exports to domestic economic growth. Through the effects of both the multiplier and the accelerator, output expands by a multiple of the initial value of exports. Exportation also tends to reduce the opportunity cost of domestic resources by providing foreign exchange necessary to meet domestic demands from abroad at relatively lower prices. Forward and backward linkages stimulate growth in export-related activities. Export expansion, in addition, gives rise to external economies, economies of scale, an efficient allocation of resources, and a greater-than-one elasticity of expectations on the part of domestic exporters. Thus, we set out in this note to measure the labour absorptive capacity of exports and import substitution in Egypt. Our objective function which we seek to maximize (minimize) is that of labour employment (unemployment) via the foreign trade sector.
Keywords: 330